Site-specific excision repair of 1-nitrosopyrene-induced DNA adducts at the nucleotide level in the HPRT gene of human fibroblasts: effect of adduct conformation on the pattern of site-specific repair. - Wei, D (1996)
Studies showing that different types of DNA adducts are repaired in human cells at different rates suggest that DNA adduct conformation is the major determinant of the rate of nucleotide excision repair. However, recent studies of repair of cyclobutane pyrimidine dimers or benzo[a]pyrene diol epoxide (BPDE)-induced adducts at the nucleotide level in DNA of normal human fibroblasts indicate that the rate of repair of the same adduct at different nucleotide positions can vary up to 10-fold, suggesting an important role for local DNA conformation. To see if site-specific DNA repair is a common phenomenon for bulky DNA adducts, we determined the rate of repair of 1-nitrosopyrene (1-NOP)-induced adducts in exon 3 of the hypoxanthine phosphoribosyltransferase gene at the nucleotide level using ligation-mediated PCR. To distinguish between the contributions of adduct conformation and local DNA conformation to the rate of repair, we compared the results obtained with 1-NOP with those we obtained previously using BPDE. The principal DNA adduct formed by either agent involves guanine. We found that rates of repair of 1-NOP-induced adducts also varied significantly at the nucleotide level, but the pattern of site-specific repair differed from that of BPDE-induced adducts at the same guanine positions in the same region of DNA. The average rate of excision repair of 1-NOP adducts in exon 3 was two to three times faster than that of BPDE adducts, but at particular nucleotides the rate was slower or faster than that of BPDE adducts or, in some cases, equal to that of BPDE adducts. These results indicate that the contribution of the local DNA conformation to the rate of repair at a particular nucleotide position depends upon the specific DNA adduct involved. However, the data also indicate that the conformation of the DNA adduct is not the only factor contributing to the rate of repair at different nucleotide positions. Instead, the rate of repair at a particular nucleotide position depends on the interaction between the specific adduct conformation and the local DNA conformation at that nucleotide.